1986
DOI: 10.1007/bf00455845
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of the etiology of tendon rupture

Abstract: Native collagen fibers were exposed to different dynamic loads to simulate damage to tendons and ligaments relevant clinically and for sports medicine. The results suggest that the rupture of a tendon is caused at the submicroscopic fibrillar level. Not only slow or very fast elongation, but also very fast unloading of stretched fibers seems to be responsible for disseminated damage, which reduces the stability of a fiber. This damage is induced by intrafibrillar sliding processes, which occur only a few secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Recent investigations suggest that a significant cause of rupture of the Achilles tendon m a y be repeated microtrauma [9,11,19]. Experiments have shown that during stress structural disturbances with sliding of the fibrous tissue takes place before rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations suggest that a significant cause of rupture of the Achilles tendon m a y be repeated microtrauma [9,11,19]. Experiments have shown that during stress structural disturbances with sliding of the fibrous tissue takes place before rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The manifestation of tendinopathy is commonly ascribed to the progression of cumulative microtrauma to higher structural levels of the tissue and successive matrix breakdown (Kannus, 1997 ; Cook and Purdam, 2009 ). The degenerative cascade might also be related to the discontinued mechanotransduction of ruptured fibrils (Knörzer et al, 1986 ) and the associated catabolic responses of under-stimulated fibroblasts (Arnoczky et al, 2007 ). As both scenarios (i.e., mechanical over- or understimulation) are based on initial strain-induced damage, it seems plausible that an imbalanced adaptation of muscle and tendon could increase the risk of overload-induced tendinopathy.…”
Section: Implications and Concepts For Preventionmentioning
confidence: 99%
“…However, especially in the case of modeling arterial failure, a phenomenological model for anisotropic damage is limiting. In this study, we implemented an elastoplastic formulation of collagen fiber damage based on observations made during uniaxial tension experiments and reported studies on tendons [48, 49].…”
Section: Discussionmentioning
confidence: 99%